PENGARUH ENVIRONMENTAL PERFORMANCE, STRUKTUR MODAL, DAN BIAYA LINGKUNGAN TERHADAP PROFITABILITAS - Deby Terra Amalia; Hermi Hermi (EBID: Ekonomi Bisnis Digital, 2025)
This study examines the effect of Environmental Performance, Capital Structure, and Environmental Costs on Profitability (ROE) in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. This study uses Purposive Sampling with 111 observations. This is a quantitative study employing panel data regression analysis processed using Eviews 12. The results indicate that only Environmental Performance has a positive impact on ROE, while Capital Structure and Environmental Costs do not have a significant effect. These findings are expected to serve as a reference for management in sustainability strategies and for investors in making environmentally-based investment decisions.